ESRA19-0517 Combined spinal-epidural anaesthesia for emergency bowel resection in a patient with a large lung tumour. (30th August 2019) - Lim, R; Lim, ML; Thangavelautham, S
Abstract : Background and aims: Intrathoracic masses require special anaesthetic consideration as they may cause mechanical compression on the airways or the great vessels, possibly resulting in acute respiratory and hemodynamic insufficiency. These effects can be caused or worsened by sedation and paralysis during induction of general anaesthesia (GA) and/or changes in position during surgery. We describe a case of successful combined spinal-epidural (CSE) for laparotomy in a patient with mediastinal mass, thereby avoiding GA. Methods: An 80-year-old female admitted for incarcerated right inguinal hernia with bowel ischaemia was listed for emergency open repair of right inguinal hernia keep in view bowel resection and stoma. Incidentally, she had a newly discovered right upper lung mass measuring 7.4 cm with compression on the mediastinum including the SVC. CSE was done at L3/4 in the right lateral position. Intrathecal 2.5 ml of 0.5% heavy Bupivacaine with 15mcg Fentanyl was given. The epidural catheter was inserted and secured. Results: Surgery began with an inguinal skin incision 15 minutes after CSE. Epidural top-up of 2 ml 0.75% Ropivacaine was given 20 and 60 minutes into the surgery. 15 cm of unhealthy small bowel was resected and an anastomosis done. The patient was sedated with intravenous propofol infusion and remained comfortable and hemodynamically stable throughout the 2h surgery. She was discharged to the general ward from recovery. The catheter was removed on postoperative day 3 and she was discharged home on postoperative day 6. Conclusions: CSE is an anaesthetic technique that should be considered for patients requiring laparotomy who have intrathoracic masses with risk of mass effect under GA.